Mengatasi Dampak Negatif Diskalkulia Dalam Menyelesaikan Masalah Matematika - Suzana, Yenny; Maulida, Iyana (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2019)
Dyscalculia is a mathematics learning disorder in children who have difficulty counting and calculating. Children who have dyscalculia will show difficulty in doing assignments involving numbers and mathematical symbols. Children with dyscalculia are unable to digest questions and do mathematical processes, or understand abstract questions. So children with dyscalculia cannot solve math problems like children in general. So that to overcome these negative impacts, with dyscalculous disorders can more easily understand and solve math problems.